A step toward restoring hand functions in patients with multiple sclerosis—a study protocol - Zoghi, Maryam; Jaberzadeh, Shapour (Frontiers in Rehabilitation Sciences, 2023)
Multiple sclerosis (MS) is an autoimmune disease that produces lesions throughout the central nervous system in both gray and white matter with demyelination of axons and oligodendrocyte loss and resulting neurological dysfunctions. The improvement of hand functions was the least targeted area of neurorehabilitation research. In this study, we propose a whole new approach for improving hand functions compared to the current neurorehabilitation strategies. It has been shown that myelination is not necessary for recalling a previously learned skill. However, this process of “production of oligodendrocytes and myelin” can be triggered by learning new skills in the motor cortex (M1) which is a crucial mechanism for neuroplasticity. Over the past two decades, transcranial direct current stimulation (tDCS) has been used as a neuromodulatory technique to enhance motor learning and motor functions in health and disease in human subjects. As tDCS induces a non-specific effect, it is generally agreed that a-tDCS-dependent behavioral gains can be optimized with concurrent behavioral training. Literature indicates that the application of tDCS during motor learning can have priming effects on long-term potentiation mechanism of its action and prolong the effects of motor training in health and disease. In this study, we propose to assess whether applying within-session repeated a-tDCS on M1 during learning a new motor skill can be more effective in improving hand functions in patients with MS compared to current neurorehabilitation strategies. If learning a new motor skill shows more improvement in hand functions in patients with MS, this approach can be adopted by all clinicians as a new approach to restoring the hand functions in this population. Furthermore, if the application of a-tDCS shows to have an accumulative effect in improving hand functions in patients with MS, tDCS may provide an adjunct intervention during rehabilitation for these patients.